LiPAA with Short‐chain Anion Facilitating Li2Sx (x ≤ 4) Reduction in Lean‐electrolyte Lithium–sulfur Battery. Issue 3 (28th June 2021) - Zhang, Jizong; Chen, Mingming; Si, Yu; Guo, Jian; Wu, Tianli; Wang, Chengyang; Wang, Xiaolei
Abstract : Lean electrolyte usage in lithium–sulfur battery (LSB) meets the demand of the high energy density. However, lean condition makes the electrolyte‐related interface discrete, leading to retardation of ion transfer that depends on interfaces. Consequently, electrochemical reactions face restraint. Herein, lithium polyacrylate acid (LiPAA) with short‐chain anions (molecular weight of 2000) is introduced into the cathode. Because of the polysulfide (PS)‐philic instinct of the short‐chain PAA anions, short‐chain PS is captured inside of the cathode. In addition, LiPAA supplies Li + to the short‐chain PS captured. The strong interaction between Li2 S4 and LiPAA effectively decreases Li2 S4 migration to the anode during discharging. In a sense, the ion mass transfer pattern is thus changed comparing to traditional long‐way mode between cathode and anode. Galvanostatic intermittent titration technique (GITT) proves that the interfacial reaction resistance is greatly decreased in the region where Li2 S x ( x  ≤ 4) reduction contributes most. In the same time, the reversibility of electrochemical reduction/oxidation is improved. Owing to the accelerated Li2 S x ( x  ≤ 4) reduction, Li implanting of only 0.3 wt.% plus O introduction up to 1.4 wt.% enables the LSB perform well even with 1/4 of regular electrolyte dosage (5 μL mg −1 ) and high‐sulfur loading (4.2 mg cm −2 ), increasing its rate capacity C 0.8/0.5 from 52.6% (without the LiPAA) to 92.3% (with the LiPAA) as well as a capacity of 518.7 mAh g −1 after 400 cycles at 0.8 mA cm −2 . Abstract : The anions of short‐chain LiPAA attract and capture polysulfides (PS) to its Li + cations. Therefore, the interfacial reaction resistance in the region where Li2 S x ( x  ≤ 4) reduction contributes most is decreased, boosting the electrochemical performances.